2021
DOI: 10.1002/tox.23114
|View full text |Cite
|
Sign up to set email alerts
|

Parental PM2.5 exposure changes Th17/Treg cells in offspring, is associated with the elevation of blood pressure

Abstract: Epidemiological evidences have indicated that fine particulate matter (PM 2.5 ) exposure is associated with the occurrence and development of hypertension. The present study aims to explore the effects of parental PM 2.5 exposure on blood pressure in offspring and elucidate the potential mechanism. The parental male and female C57BL/6 mice were exposed to concentrated PM 2.5 or filtered air (FA) using Shanghai Meteorological and Environmental Animal Exposure System (Shanghai-METAS) for 16 weeks. At week 12, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The earliest AHR agonists identified were typically constituents of environmental chemicals including dioxins, BPA, phthalates, and PFOS, as well as polycyclic aromatic hydrocarbons [143]. Various chemicals have been assessed, including TCDD [117][118][119][120][121], BPA [122][123][124][125][126], DEHP [127][128][129], DBP [130,131], perfluorooctane sulfonic acid (PFOS) [132], BaP [133], Cd [134][135][136], and PM 2.5 [137,141]. Maternal exposure to the AHR ligand TCDD induces hypertension in offspring, correlated with AHR/CYP1A1 induction and TH17mediated renal inflammation [118].…”
Section: Evidence From Animal Models: the Role Of Ahr In Ckm Programmingmentioning
confidence: 99%
“…The earliest AHR agonists identified were typically constituents of environmental chemicals including dioxins, BPA, phthalates, and PFOS, as well as polycyclic aromatic hydrocarbons [143]. Various chemicals have been assessed, including TCDD [117][118][119][120][121], BPA [122][123][124][125][126], DEHP [127][128][129], DBP [130,131], perfluorooctane sulfonic acid (PFOS) [132], BaP [133], Cd [134][135][136], and PM 2.5 [137,141]. Maternal exposure to the AHR ligand TCDD induces hypertension in offspring, correlated with AHR/CYP1A1 induction and TH17mediated renal inflammation [118].…”
Section: Evidence From Animal Models: the Role Of Ahr In Ckm Programmingmentioning
confidence: 99%
“…These findings demonstrated that PM 2.5 can induce inflammatory responses in which macrophages and neutrophils are involved [ 184 ]. Other studies have suggested that parental PM 2.5 could mediate Th17- and T regular-related immune microenvironment changes, leading to increased blood pressure in offspring [ 185 ]. In vitro, studies have shown that PM 2.5 may exacerbate viral myocarditis through MMP-2/TIMP-1 imbalance, perforin response and Th17-mediated viral replication [ 186 ].…”
Section: The Effects and Mechanisms Of Pm On Neurologic Systemmentioning
confidence: 99%
“…Table 3 summarizes animal studies demonstrating the association between maternal environmental chemical exposure and subsequent kidney disease and hypertension in progeny ( 91 105 ). The current review is solely restricted to chemical exposures happening during the duration of kidney development, with a focus on reporting offspring outcomes starting after birth.…”
Section: Prenatal Environmental Chemical Exposure On Renal Programmingmentioning
confidence: 99%
“…Several types of chemicals have been evaluated, including TCDD ( 88 90 ), BPA ( 94 , 95 ), DEHP ( 96 ), DBP ( 97 , 98 ), BaP ( 99 ), heavy metal mixture ( 100 ), Cd ( 101 103 ), and PM 2.5 ( 104 , 105 ). Maternal exposure to TCDD or BPA causes the rise of BP in adult rat offspring ( 91 , 92 , 94 ), which was relevant to dysregulated AHR signaling pathway.…”
Section: Prenatal Environmental Chemical Exposure On Renal Programmingmentioning
confidence: 99%
See 1 more Smart Citation